High-Power Optics : Lasers and Applications - Apollonov, Victor V. (Springer Series in Optical Sciences,, 2015)
This book covers the basics, realization and materials for high power laser systems and high power radiation interaction with  matter. The physical and technical fundamentals of high intensity laser optics and adaptive optics and the related physical processes in high intensity laser systems are explained. A main question discussed is: What is power optics? In what way is it different from ordinary optics widely used in cameras, motion-picture projectors, i.e., for everyday use? An undesirable consequence of the thermal deformation of optical elements and surfaces was discovered during studies of the interaction with powerful incident laser radiation. The requirements to the fabrication, performance and quality of optical elements employed within systems for most practical applications are also covered. The high-power laser performance is generally governed by the following: (i) the absorption of incident optical radiation (governed primarily by various absorption mechanisms), (ii) followed by a temperature increase and response governed primarily by thermal properties and (iii)  the thermo-optical and thermo-mechanical response of  distortion, stress, fracture, etc. All this needs to be understood to design efficient, compact, reliable and useful high power systems for many applications under a variety of operating conditions, pulsed, continuous wave and burst mode of varying duty cycles. The book gives an overview of an important spectrum of related topics like laser resonator configurations, intermetallic optical coatings, heat carriers for high power optics, cellular materials, high-repetition-rate lasers and mono-module disk lasers for high power optics.